What is the value of testing for tick-borne diseases in cattle in endemic areas? A case study of bovine anaplasmosis - Valeria Paucar-Quishpe; Dirk Berkvens; Ximena Pérez-Otáñez; Richar Rodríguez-Hidalgo; Darío Cepeda-Bastidas; Cecilia Perez; Yadira Guasumba; Daniela Balseca; Kamilo Villareal; María-Augusta Chávez-Larrea; Sandra Enríquez; Jorge Grijalva; et al. (PLoS ONE, 2025)
Anaplasmosis is a tick-borne disease (TBDs) caused by Anaplasma spp. In areas where TBDs are endemic, it is crucial to consider the animals’ immunological status in relation to these diseases. The true prevalence of bovine anaplasmosis, the percentage of animals with protective antibodies against this TBD, and the diagnostic characteristics of three tests (multiplex polymerase chain reaction (mPCR), competitive-inhibition enzyme-linked immunosorbent assay (cELISA), and blood smear (BS)) were estimated using a Bayesian approach. A total of 620 samples were collected in two subtropical areas of Ecuador. A significant finding of this study is that approximately 70% of cattle in those endemic areas harbored protective antibodies against Anaplasma marginale. This elevated percentage may stem from persistent exposure with a high pathogen prevalence in ticks. The decline in cELISA specificity must be attributed to cross-reactivity with protective antibodies against Anaplasma spp. It is crucial to interpret this test outcome alongside exposure history and clinical manifestations. The elevated apparent prevalence detected by cELISA and BS should be contextualized with mPCR results. The high seroprevalence and infrequent clinical outbreaks suggest that the pathogen has achieved endemic stability. This study provides valuable insights into the dynamics of anaplasmosis in endemic areas and may serve as a foundation for devising TBDs control strategies in these areas.